Smoking cessation and associated factors during pregnancy Cese del consumo de tabaco durante el embarazo y factores asociados - Matías Torrent; Jordi Sunyer; Paul Cullinan; Xavier Basagaña; Jessica Harris; Oscar García; Josep Maria Antó (Elsevier, 2004)
Objective: To examine smoking habits before and during pregnancy, as well as factors associated with smoking cessation, in three European settings. Methods: Women seeking antenatal care in Ashford (UK), Minorca and Barcelona (Spain) were recruited to the Asthma Multicenter Infant Cohort Study (AMICS). Questionnaires inquiring into the smoking habits of each woman and her partner, demographic data, occupation, educational level, number of previous children, breast feeding, alcohol intake, and history of asthma and of other allergic diseases were completed during pregnancy and in the first year after delivery. Results: A total of 1 572 pregnant women were included in the three cohorts. Smoking prior to pregnancy was more common in Barcelona (46.2%) than in Minorca (39.8%) or Ashford (31.6%). Cessation rates during pregnancy also differed: 18% of women in Ashford, 20.4% in Minorca and 31.9% in Barcelona were still smoking during the first trimester. In a multivariate regression model, the factors showing a significant (negative) association with smoking cessation during pregnancy were having older children, having a partner who smoked and starting smoking at a young age. Conclusions: Baseline smoking habits and changes in smoking habits during pregnancy significantly differed between the three communities studied. Women pregnant with their first child, those who had started smoking at a later age and those whose partners were non-smokers were more likely to stop smoking when pregnant. Objetivo: Describir el hábito tabáquico antes y durante el embarazo y los factores asociados con su cese con relación al embarazo en distintos entornos europeos. Métodos: Se ha incluido en el estudio a las mujeres captadas durante el embarazo para participar en el estudio AMICS (Asthma Multicentre Infant Cohort Study) en Ashford (Reino Unido), Barcelona y Menorca (España). Se administró un cuestionario durante el embarazo y otro durante el primer año posparto, que incluía los siguientes aspectos: hábito tabáquico de la mujer y de su compañero, datos demográficos, ocupación, nivel de estudios, número de hijos previos, lactancia materna, consumo de alcohol e historia de asma y otras enfermedades alérgicas. Resultados: Entre las 3 cohortes se incluyó a un total de 1.572 mujeres. Antes del embarazo, el porcentaje de mujeres fumadoras fue mayor en Barcelona (46,2%) que en Menorca (39,8%) o Ashford (31,6%). Las tasas de abandono del hábito tabáquico en relación con el embarazo también variaron en cada cohorte, de manera que durante el primer trimestre de embarazo continuaron fumando el 18% en Ashford, el 20,4% en Menorca y el 31,9% en Barcelona. En un modelo de regresión múltiple, tener hijos previos, que el compañero sea fumador y haber empezado a fumar más joven muestran una asociación (negativa) con la probabilidad de abandonar el tabaco en relación con el embarazo. Conclusiones: El consumo de tabaco antes y durante el embarazo muestra importantes diferencias en las 3 comunidades estudiadas. Las mujeres en su primer embarazo, que empezaron a fumar más tardíamente y cuyo compañero no fuma son las que con mayor frecuencia abandonan el tabaco al quedarse embarazadas.